2012
DOI: 10.1161/hypertensionaha.112.194167
|View full text |Cite
|
Sign up to set email alerts
|

Initial Monotherapy and Combination Therapy and Hypertension Control the First Year

Abstract: Initial antihypertensive therapy with single-pill combinations produced more rapid blood pressure control than initial monotherapy in clinical trials. Other studies reported better cardiovascular outcomes in patients achieving lower blood pressure during the first treatment year. We assessed the effectiveness of initial antihypertensive monotherapy, free combinations, and single-pill combinations in controlling untreated, uncontrolled hypertensives during their first treatment year. Electronic record data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
1
25

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(134 citation statements)
references
References 28 publications
5
103
1
25
Order By: Relevance
“…A previous study in South Carolina showed that 74.2% of patients received one antihypertensive pill and medication category. 5 This might be because the target blood pressure could be obtained Note:ACEI= Angiotensin-converting enzyme inhibitor using a single drug therapy. From the current study, a single drug therapy with ACE inhibitors (58.62%) was more strongly associated with good control of blood pressure than monotherapy with beta-blockers, CCBs, diuretics, or the use of multiple drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in South Carolina showed that 74.2% of patients received one antihypertensive pill and medication category. 5 This might be because the target blood pressure could be obtained Note:ACEI= Angiotensin-converting enzyme inhibitor using a single drug therapy. From the current study, a single drug therapy with ACE inhibitors (58.62%) was more strongly associated with good control of blood pressure than monotherapy with beta-blockers, CCBs, diuretics, or the use of multiple drugs.…”
Section: Discussionmentioning
confidence: 99%
“…В настоящее время 74,2% пациентов используют монотерапию, 17,2% СК и только 8,6% ФК [29]. С комбинации антигипертензивных препаратов начинают лечение лишь 25,8% пациентов АГ [29].…”
Section: Hemodynamic Stability Of Hypertension Patient: Triple Therapunclassified
“…С комбинации антигипертензивных препаратов начинают лечение лишь 25,8% пациентов АГ [29]. В сравнении с монотерапией, инициация АГТ в режиме СК позволяет лучше контролировать АД на 34% (ОР 1,34; ДИ 1,31-1,37), а в режиме ФК на 53% (ОР 1,53; ДИ 1,47-1,58) [29].…”
Section: Hemodynamic Stability Of Hypertension Patient: Triple Therapunclassified
See 1 more Smart Citation
“…69 treatment of hypertension appears beneficial in terms of BP 70 control and CV event reduction [8,9]. Combining two 71 antihypertensive agents from different classes has also 72 been shown to be a more effective way of reducing BP than 73 doubling the dose of a single agent [10].…”
mentioning
confidence: 99%